2009
DOI: 10.1111/j.1532-5415.2009.02221.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Suspected Elder Abuse Subtypes in People Aged 75 and Older

Abstract: After adjustment for confounding factors, each subtype of suspected elder abuse was associated with different variables. The results of this study suggest that elder abuse cannot be analyzed as a unitary concept and that risk factors must be assessed for each abuse subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
4
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 27 publications
6
79
4
8
Order By: Relevance
“…The study of Li Wu, showed that the elderly people who live alone usually experience higher levels of abuse (28), and other studies indicated that being widowed can be considered as the high risk for experiencing abuse (39); this may result from the fact that cohabitation increases the risk of conflicts and contacts; therefore, the level of abuse may increase in contrast. In the current study, elderly men were at higher risk of abuse than women; while, in the studies of Li Wu, Garre, and Nowrouzi women had experienced higher abuse (28,40,41). This difference may result from different sampling methods, more men rather women in the population under study, or elderly women are more respectable and usually experience lower levels of abuse; since they do house hold responsibilities such as cooking or taking care of grandchildren.…”
Section: Discussioncontrasting
confidence: 38%
“…The study of Li Wu, showed that the elderly people who live alone usually experience higher levels of abuse (28), and other studies indicated that being widowed can be considered as the high risk for experiencing abuse (39); this may result from the fact that cohabitation increases the risk of conflicts and contacts; therefore, the level of abuse may increase in contrast. In the current study, elderly men were at higher risk of abuse than women; while, in the studies of Li Wu, Garre, and Nowrouzi women had experienced higher abuse (28,40,41). This difference may result from different sampling methods, more men rather women in the population under study, or elderly women are more respectable and usually experience lower levels of abuse; since they do house hold responsibilities such as cooking or taking care of grandchildren.…”
Section: Discussioncontrasting
confidence: 38%
“…Elder abuse is common, is often not recognized by health providers, directly affects quality of life, and is associated with increased health care utilization. [59][60][61][62] EPs and nurses did not identify abuse among any of the nine patients who reported abuse occurring at some point in the past year. This may be because the abuse was not the cause of this ED visit or not an ongoing concern, questions that were not asked in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To assess psychological abuse, the following two questions were used: 'Have you been verbally offended during the past 12 months?' (with response alternatives [1] 'No', [2] 'Yes, sometimes' and [3] 'several times') and 'Have you been exposed to any threats or threats of violence that made you scared during the past 12 months?' (with binary answer alternatives).…”
Section: Methodsmentioning
confidence: 99%
“…As one source puts it, 'The incidents differ -the burning of a so called witch in Mozambique, the punching of a nursing home resident in the USA, the violent robbery of a fruit-seller in Brazil -but they share a common factor: all are examples of abuse against elderly people…' 2 . Elder abuse is often defined as any action, or any lack of appropriate action, that causes harm, intentionally or unintentionally, to an elderly person 3 . The main types of abuse that have been identified are physical, psychological or emotional, sexual and financial abuse, and negligence 1,4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation